Bio-based polymer nanocomposites based on nylon 11 and WS2 inorganic nanotubes. Issue 23 (13th March 2015) - Naffakh, Mohammed; Shuttleworth, Peter S.; Ellis, Gary
<x xml:space="preserve">Abstract</x> This study confirms the potential use of novel bio-nylon 11/INT-WS2 for many eco-friendly and biomedical applications.